(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The emergences of cloud computing deals in various internet applications developers for hosting various applications which users are in need in this day to day life.the idea is cloud ontology for easy Selection, Publication and Discovery in cloud services. Query Processing Agent, Ontological Similarities.In this paper, purposal is an cloud service discovery system with ontological model, in order to solve,for example: A job site, It’s not an ordinary jobsite but focusing and specializing in matching the users or clients queries related to jobs and displaying the information even by giving options of updating their information which is needed for this Job Domain. This paper implements the cloud ontology technique to make cloud service discovery system efficient for user query in job site. The aim of this paper is to determine how the CSDS with the Cloud ontology achieved better performance than the CSDS without the Cloud ontology. By consulting a Cloud ontology to reason and to rating about the relations among Cloud services, the CSDS is more successful in locating Cloud services and more likely to discover Cloud services that meet consumers‟ requirements.